DOI: 10.14232/phd.10146
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Effect of Psychosocial Interventions in Breast Cancer

Abstract: were found to be possible contributing factors to the increase in long-term quality of life. Conclusions The results show that the timely detection and proper management of psychological distress and the enhancement of posttraumatic growth are of great value, as they might be important contributing factors to long-term quality of life in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
3
4
1
Order By: Relevance
“…28 Authors of another study emphasized that psychosocial interventions among breast cancer patients undergoing surgical procedures reduced their fear of the short-term outcomes of the procedure. 29 In this study, we identified that surgical fear levels were relatively high compared to other study results, and that fear is experienced more in the preoperative period, similar to other the studies. 27,29 Patients' anxiety levels decrease with individual education, informative brochures, or audio materials during the preoperative period.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…28 Authors of another study emphasized that psychosocial interventions among breast cancer patients undergoing surgical procedures reduced their fear of the short-term outcomes of the procedure. 29 In this study, we identified that surgical fear levels were relatively high compared to other study results, and that fear is experienced more in the preoperative period, similar to other the studies. 27,29 Patients' anxiety levels decrease with individual education, informative brochures, or audio materials during the preoperative period.…”
Section: Discussionsupporting
confidence: 85%
“…29 In this study, we identified that surgical fear levels were relatively high compared to other study results, and that fear is experienced more in the preoperative period, similar to other the studies. 27,29 Patients' anxiety levels decrease with individual education, informative brochures, or audio materials during the preoperative period. 12 Nursing visits in the preoperative period that include multimedia could reduce perioperative anxiety.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Despite a widespread use in various elective surgery populations, so far only one study reported SFQ-scores of female BC patients. The SFQ, however, was not a primary outcome in that study, and so far, the results are only described in a doctoral dissertation, but not yet published in a peer-reviewed journal [24]. Finally, an interpretation of reported mean SFQ-values of this study remains difficult as these were also not discussed in the context of prior studies [24].…”
Section: Introductionmentioning
confidence: 82%
“…The SFQ, however, was not a primary outcome in that study, and so far, the results are only described in a doctoral dissertation, but not yet published in a peer-reviewed journal [24]. Finally, an interpretation of reported mean SFQ-values of this study remains difficult as these were also not discussed in the context of prior studies [24]. Among in-and outpatients undergoing various surgical procedures, fears about shortterm aspects of the upcoming surgery were shown to predict acute pain up until four days postoperatively [25,26].…”
Section: Introductionmentioning
confidence: 98%